2011
DOI: 10.1186/1475-2840-10-115
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the efficacy of miglitol and sitagliptin for type 2diabetes with a continuous glucose monitoring system and incretin-related markers

Abstract: BackgroundGlucose fluctuations including robust postprandial hyperglycemia are a risk for promoting atherosclerosis and diabetic complications. The α-glucosidase inhibitors and the dipeptidyl peptidase-4 (DPP-4) inhibitors have been found to effectively decrease postprandial hyperglycemia independently. Therefore, glycemic control with the combination of these drugs is warranted.MethodsContinuous glucose monitoring (CGM) was performed for 3 patients with type 2 diabetes and 1 control subject from the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…These effects were demonstrated precisely by the mean ± SD values and calculated AUC values of the glucose levels monitored by CGMS. The authors have previously shown that the combination of sitagliptin and miglitol was effective for reducing glucose fluctuations and stabilizing postprandial blood glucose levels in patients with type 2 diabetes receiving oral medication [19]. In the present study, the authors have demonstrated that both single administration and coadministration of these two drugs was also effective in an insulin-treated patient.…”
Section: Discussionsupporting
confidence: 58%
“…These effects were demonstrated precisely by the mean ± SD values and calculated AUC values of the glucose levels monitored by CGMS. The authors have previously shown that the combination of sitagliptin and miglitol was effective for reducing glucose fluctuations and stabilizing postprandial blood glucose levels in patients with type 2 diabetes receiving oral medication [19]. In the present study, the authors have demonstrated that both single administration and coadministration of these two drugs was also effective in an insulin-treated patient.…”
Section: Discussionsupporting
confidence: 58%
“…There are several papers reporting the additive use of DPP-4 inhibitors in cases in which α-glucosidase inhibitors proved incomplete control, analyzing combined effects of these drugs by CGM or incretin assays [17][18][19][20]. However, only few reports are available analyzing whether the additional use of α-glucosidase inhibitors provides beneficial effect on the blood glucose fluctuation and incretin hormone secretion in cases in which DPP-4 inhibitors were not sufficiently effective.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have been published regarding the usefulness of a low-carbohydrate diet and α-GI for late dumping syndrome (6)(7)(8)(9)(10)(11). Among these, four using CGM revealed that a low-carbohydrate diet and α-GI effectively decreased the frequency of hypoglycemia and the fluctuation of blood glucose after gastric surgery (5)(6)(7)11).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, four using CGM revealed that a low-carbohydrate diet and α-GI effectively decreased the frequency of hypoglycemia and the fluctuation of blood glucose after gastric surgery (5)(6)(7)11). On the other hand, there is a report that miglitol was effective for reactive hypoglycemia secondary to late dumping syndrome, but not acarbose and voglibose (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation